Mechanical and Frictional Behavior of Jute-Textile-Reinforced Polymer Composites With Matrix Modification - Farhin Tabassum; M. R. Asekin; M. Salim Kaiser; S. Reaz Ahmed (Advances in Materials Science and Engineering)
The mechanical and frictional behaviors of jute-textile-reinforced polymer composites have been investigated experimentally under the influence of matrix modification and postprocessing thermal treatments. Three different matrix modifiers, namely, carbon, silicon, and aluminum powders are considered for the modification of polymeric material used in the sandwich structured biodegradable jute-textile-reinforced composites. The modified composites are then subjected to post-processing thermal treatments isochronally at temperatures within the range of 0–250°C. Inclusion of carbon, silicon, and aluminum powders into the polyester resin leads to significant changes in the performance of the composite materials in terms of hardness, tensile, as well as wear and frictional properties. More specifically, the aluminum powders show the most promising potential to improve the properties of polyester-jute composites compared with those of silicon and carbon powders. Moreover, at the postprocessing temperature of 125°C, all the modified composite samples show their best performances in terms of hardness, strength, modulus, wear rate, and friction coefficient, which is eventually verified to be the optimum postprocessing temperature for the composites of the present type. The pin-on-disc wear study shows that under constant and varying load conditions, the coefficient of friction of the composite is found to be relatively higher for the case of aluminum-powder modifier compared with those of silicon and carbon power modifiers. The results of optical microstructures, scanning electron microscopic (SEM) images, and energy dispersive x-ray (EDX) spectra are found to be in support of the results observed through direct measurements. A quantitative comparison of the measured results verifies the relative improvement of the major mechanical and frictional properties of the composites, which, in turn, verifies the effectiveness of the selective matrix modifiers in conjunction with post-thermal treatments.